Effects of a respiratory physiotherapy session in patients with Lower Respiratory Tract Infections - Marques, Alda (2020)
Patients with lower respiratory tract infections (LRTI – acute exacerbations of obstructive/restrictive diseases) experience severe dyspnea and increasedsputum production (Woodhead, 2011). Respiratory physiotherapy (RP) has shown to improve these symptoms in chronic respiratory conditions (Garrod, 2007). However, studies exploring its effectiveness in patients with LRTI are lacking